Synthetic microbial consortia derived from rhizosphere soil protect wheat against a soilborne fungal pathogen - Yin, Chuntao; Hagerty, Christina H.; Paulitz, Timothy C. (Frontiers in Microbiology, 2022)
Synthetic microbial communities (SynComs) could potentially enhance some functions of the plant microbiome and emerge as a promising inoculant for improving crop performance. Here, we characterized a collection of bacteria, previously isolated from the wheat rhizosphere, for their antifungal activity against soilborne fungal pathogens. Ten SynComs with different compositions from fourteen bacterial strains were created. Seven SynComs protected wheat from Rhizoctonia solani AG8 infection. Further, the mechanisms of interaction of the tested bacteria with each other and plants were explored. We found that nine bacteria and nine SynComs impacted the root growth of Arabidopsis. Nine bacteria and four SynComs significantly inhibited the growth of AG8 by producing volatiles. The cell-free supernatants from six bacteria inhibited the growth of AG8. Together, this study provided the potential for improving crop resilience by creating SynComs.